Pseudo mapping of termites distribution in oil palm plantation / Mohamad Syahrul Misham - Misham, Mohamad Syahrul (Faculty of Plantation and Agrotechnology, 2015)
The objectives of the study are to evaluate of termites incidence also to record and develop termite distributions followed by the creation of a precise termites hazard maps for oil palm plantation. Termite is one of insects that have rapid reproduction. Besides, termite can be hyperactive in finding places for habitat as well as in search the food sources. This behavior leads to high population of termites in particular area. The study will be conducted in oil palm plantation at Asam Bubok, Parit Raja, Batu Pahat (l03.08198N, and 1.94918E) each rows by rows in this crop plots. The survey had been accompanied for 3 months, beginning from 23rd August 2014 finished in 25th October 2014. The method of the study will be divided into two phases. The point sample number of infestation by termites will be determined using systematic random sampling method. The first phase is the process by using Global Positioning System (GPS) model Garmin to setting coordinates point of sampling and number of termite nests and number of damp wood (decomposed fronds) was found will be physically carried out and calculations had been made on the right side only and vice versa in the next rows in the areas and nearby with a sampling point of oil palm tree. At the same time, all collection data will be recorded in a manually form. The second phase of the study is integrating the information collected from GPS device to construct a termites hazard maps using ArcGIS 10 software. From this survey, incidence maps were constructed and these maps had been categorized high because the range of percentage around 65% until 72%. In this study the hazards maps were classified into 5 stages, that is High (>40%), Moderate (30% - 40%), Low moderate (20% - 30%), low (10% -20%) and very low «10%) according to Cookson and Trajtsman, 2002.